PEMETAAN PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARANEKONOMI MATERI AKUNTANSI KELAS XI IPS SMA NEGERI 13 SURABAYA - DONI PRIHANTO (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
The purpose of this research is to know the accounting instructional media used in the learning process, knows the reason for using instructional media and knowing the feasibility of instructional media used in the learning process. This research is a type of descriptive research. Performed at the class XI Ips SMAN 13 Surabaya. The subjek of this study is the use of intrucsional media in accounting . The data was collected using a interview guide and study sheet. Feasibility test is done by the validation test of instructional media by two media experts, The results compared with the interpretation criteria. Results of this study was the use of media as well as the feasibility of media powerpoint. Instructional media declared eligible based feasibility study according to media experts with a percentage of total by 70.71%. From the result above can be concluded media the learning powerpoint worthy used as a support the learning for subjects accounting on material cycle accounting services company. Keywords: Mapping, Learning Media, Accounting